FINTECH FOR SDGS: DRIVING ECONOMIC DEVELOPMENT THROUGH FINANCIAL INNOVATION - Wicaksana, Dwi Yoga; Dewi, Hapsari Shinta Citra Puspita; Erta, Erta (Journal of Digital Business and Innovation Management, 2023)
This research delves into the pivotal role of Financial Technology (FinTech) in advancing the financial sector, sustainable development, and financial inclusion. Employing a descriptive-qualitative approach and the systematic literature review (SLR) method, the study investigates FinTech's interplay with Sustainable Development, Financial Inclusion, and Economic Development globally. A meticulous Scopus search utilizing keywords like "Fintech," "SDGs," "Financial Inclusion," and "Economic Development" ensures a thorough review of pertinent literature. The results underscore FinTech's substantial impact on Sustainable Development, Financial Inclusion, and Economic Development, acting as a crucial catalyst for financial inclusion and mediating sustainable growth through financial literacy. Furthermore, FinTech exhibits the potential to underpin sustainable economic growth, financial inclusion, and Economic Development by enhancing financial service accessibility, reducing poverty, and fostering gender equality. Challenges persist, particularly in the Pacific region, where issues of accessibility, awareness, literacy, and trust impede FinTech adoption. The study advocates for awareness campaigns, financial education, and infrastructure development to surmount these obstacles. In conclusion, while FinTech significantly influences financial inclusion and economic growth, its broader impact on Sustainable Development, Financial Inclusion, and Economic Development necessitates careful consideration. The research emphasizes the imperative for interdisciplinary collaboration, global cooperation, and vigilant strategies to address challenges and leverage opportunities arising from the rapid integration of digital financial services for inclusive and sustainable Economic Development.